Pengaruh Dosis Pupuk Kandang Kambing dan Konsentrasi Pupuk Organik Cair (POC) terhadap Pertumbuhan dan Hasil Tanaman Kacang Panjang (Vigna sinensis L): Kacang Panjang, pertumbuhan, hasil, pupuk. - Uswatun, Hanifah; Santosa, Sartono Joko; Triyono, Kharis (innofarm, 2024)
This study is titled â€œThe Effect of Goat Manure and Liquid Organic Fertilizer (POC) Doses on the Growth and Yield of Long Beans (Vigna sinensis L.).â€ The aim of this research is to explore the response and interaction between goat manure and organic fertilizer (Nasa) in the context of the growth and yield of long beans. The research was conducted from October 24, 2023, to January 15, 2024, at the Agrotechnology Innovation Center of Gadjah Mada University (PIAT UGM) in Yogyakarta. The method used was a Completely Randomized Block Design (CRBD) with two treatment factors. The first factor is the dose of goat manure (K), consisting of four levels: K0 (no manure), K1 (10 tons/ha), K2 (20 tons/ha), and K3 (30 tons/ha). The second factor is the dose of Nasa liquid organic fertilizer (N), which also has four levels: N0 (no POC Nasa), N1 (10 ml/L), N2 (20 ml/L), and N3 (30 ml/L), with an application volume of 200 ml per plant. The observed parameters includeincludee plant height, number of leaves, fresh biomass weight, dry biomass weight, root length, pod length, pod weight, and number of pods. The results show that (1) the application of goat manure has a significant effect on fresh biomass weight, (2) the application of POC Nasa did not show significant differences in all observed parameters, and (3) there was no interaction between the doses of goat manure and POC Nasa on all tested parameters. keywords : Long beans, growth, yield, fertilizer